MENGUBAH BOTOL BEKAS MENJADI KARYA SENI DI KELAS III MIN 3 KOTA PALANGKARAYA - Salsabilla Johan Ajijah; Tasya Maulida; Istiyati Mahmudah (JIP: Jurnal Ilmu Pendidikan, 2025)
The activity of transforming used plastic bottles into artworks in the third-grade class at MIN 3 Kota Palangka Raya aims to enhance students' creativity while fostering environmental awareness. Using the Project Based Learning (PjBL) model, students are actively engaged in planning, executing, and evaluating the creation of art pieces from recycled bottles. This activity not only sharpens students' fine motor skills and creativity but also cultivates positive character traits such as teamwork, responsibility, and environmental concern. Beyond its educational benefits, the activity also positively impacts the environment by reducing plastic waste and opening opportunities for creative economic initiatives. Overall, this activity serves as an effective strategy for integrating art education, character building, and environmental awareness in elementary schools.